THE FEASIBILITY OF HEYZINE-BASED E-FLIPBOOK MEDIA FOR KINGDOM MONERA SUB-MATERIAL - Annisa Nabilah Mufidah; Eko Sri Wahyuni; Laili Fitri Yeni (BIOMA : Jurnal Ilmiah Biologi, 2025)
E-flipbook media is one of the audio-visual media presented in HTML format. It can be presented by using the online application service, Heyzine. The e-flipbook presents the results of the antibacterial test of thorny bajakah stem extract (Caesalpinia sumatrana Roxb.) against Salmonella typhi and its related to the kingdom monera sub-material in the tenth grade senior high school. The research was conducted as descriptive quantitative with the presentation of data from the analysis of media feasibility. The data of media feasibility was collected in the form of a validation sheet conducted by 5 validators using a Likert scale with 5 aspects of validation, namely format, content, language, practicality, and effectiveness of the media. The feasibility test results show an average Aiken’s V value of 0.88 valid category with an ICC value of 0.863 very good category. Based on the results of this research, it can be concluded that e-flipbook is suitable for use as a learning media in schools.